ABC transporter mis-splicing associated with resistance to Bt toxin Cry2Ab in laboratory- and field-selected pink bollworm - Mathew, Lolita G. (Sci Rep, 2018)
Evolution of pest resistance threatens the benefits of genetically engineered crops that produce Bacillus thuringiensis (Bt) insecticidal proteins. Strategies intended to delay pest resistance are most effective when implemented proactively. Accordingly, researchers have selected for and analyzed resistance to Bt toxins in many laboratory strains of pests before resistance evolves in the field, but the utility of this approach depends on the largely untested assumption that laboratory- and field-selected resistance to Bt toxins are similar. Here we compared the genetic basis of resistance to Bt toxin Cry2Ab, which is widely deployed in transgenic crops, between laboratory- and field-selected populations of the pink bollworm (Pectinophora gossypiella), a global pest of cotton. We discovered that resistance to Cry2Ab is associated with mutations disrupting the same ATP-binding cassette transporter gene (PgABCA2) in a laboratory-selected strain from Arizona, USA, and in field-selected populations from India. The most common mutation, loss of exon 6 caused by alternative splicing, occurred in resistant larvae from both locations. Together with previous data, the results imply that mutations in the same gene confer Bt resistance in laboratory- and field-selected strains and suggest that focusing on ABCA2 genes may help to accelerate progress in monitoring and managing resistance to Cry2Ab.